Let Chen's age be \( a \). Since they are each born 1 year apart, we can express the ages of the others as follows:
- Chen (youngest): \( a \)
- Bo: \( a + 1 \)
- Mei: \( a + 2 \)
- Huan (oldest): \( a + 3 \)
Now, we can write the equation for the sum of their ages:
\[ a + (a + 1) + (a + 2) + (a + 3) = 74 \]
Simplifying this equation:
\[ 4a + 6 = 74 \]
Now, we can restructure it to:
\[ 4a = 74 - 6 \] \[ 4a = 68 \]
Therefore, the equation that can be used to determine the age of Chen is:
\[ 4a + 6 = 74 \]